Development of metalaxyl resistance in Psuedoperonospora cubensis and its management with novel action fungicides - S. RAHEJA and C. MOHAN, T.S. THIND*, S. GOSWAMI, R. KAUR (Indian Phytopathology, 2010)
Phenylamide fungicides like metalaxyl-based formulations are frequently applied to manage downy mildew of cucurbits in Punjab. Sensitivity changes to metalaxyl in Pseudoperonospora cubensis populations collected from cucumber and muskmelon fields were monitored during 2007 and 2008. Maximum number of sporangial populations (12 out of 25) exhibiting resistant response were collected in district Amritsar with ED90 values of metalaxyl ranging between 30-150 Âµg/ml and resistance factor (RF) between 6-30. Most of the populations from Jalandhar and Kapurthala showed normal sensitive response. Resistant populations possessed normal pathogenic potential and exhibited strong competitive fitness when inoculated in mixture with sensitive populations. Resistant populations did not show cross resistance to fungicides with different modes of action such as azoxystrobin, cymoxanil, dimethomorph, fluopicolide, propamocarb, chlorothalonil and mancozeb. These fungicides were also found effective against metalaxyl resistant populations under field condition and can form a part of the strategy to manage metalaxyl resistance in practice.